2009
DOI: 10.1017/s1049023x00007251
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Risk Factors in the Emergency Medical Services

Abstract: Introduction:During a medical emergency, the American public often relies on the expertise of emergency medical technicians (EMTs). These professionals face a number of occupational hazards, and the literature suggests that EMTs are at a greater risk of developing physical and mental stress-related disorders. The purpose of this paper is to systematically examine gaps in the extant literature and to present a theoretically driven conceptual model to serve as a basis for future intervention and research efforts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 71 publications
4
72
2
2
Order By: Relevance
“…personnel, including nurses, use drugs and alcohol to cope with traumatic stress [26]. Moreover, Duffy et al found that ED nurses who reported high levels of STS symptoms use alcohol as coping strategy to manage the STS symptoms [1].…”
Section: Consequences Of Sts On Ed Nursesmentioning
confidence: 99%
“…personnel, including nurses, use drugs and alcohol to cope with traumatic stress [26]. Moreover, Duffy et al found that ED nurses who reported high levels of STS symptoms use alcohol as coping strategy to manage the STS symptoms [1].…”
Section: Consequences Of Sts On Ed Nursesmentioning
confidence: 99%
“…The illness and injury data is not unforseen as there are obviously exposure risks and hazards associated with the prehospital environment (34,35). While AV have a number of policies in place to decrease the risk and Universities teach optimal occupational health and safety practices prior to the commission of any placement, these issues may still occur.…”
Section: Discussionmentioning
confidence: 99%
“…to chronic work conditions like supervisor or peer conflict, lack of support, etc. [1] Frequent and repeated exposures to these events in prehospital milieu can lead to stress reactions like posttraumatic stress disorder (PTSD). [1,2] Exposure to workrelated stressors has been found to be associated with post-traumatic stress symptoms amongst EMS.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Frequent and repeated exposures to these events in prehospital milieu can lead to stress reactions like posttraumatic stress disorder (PTSD). [1,2] Exposure to workrelated stressors has been found to be associated with post-traumatic stress symptoms amongst EMS. [2] Studies of PTSD among ambulance workers from developed countries (like Sweden, Canada, USA, U.K.) reports prevalence to be in range from 4% to 22%.…”
Section: Introductionmentioning
confidence: 99%